Mortality Prediction in Cerebral Hemorrhage Patients Using Machine Learning Algorithms in Intensive Care Units - Nie, Ximing; Cai, Yuan; Liu, Jingyi; Liu, Xiran; Zhao, Jiahui; Yang, Zhonghua; Wen, Miao; Liu, Liping (Frontiers in Neurology, 2021)
Objectives: This study aims to investigate whether the machine learning algorithms could provide an optimal early mortality prediction method compared with other scoring systems for patients with cerebral hemorrhage in intensive care units in clinical practice. Methods: Between 2008 and 2012, from Intensive Care III (MIMIC-III) database, all cerebral hemorrhage patients monitored with the MetaVision system and admitted to intensive care units were enrolled in this study. The calibration, discrimination and risk classification of predicted hospital mortality based on machine learning algorithms were assessed. The primary outcome was hospital mortality. Model performance was assessed with accuracy and receiver operating characteristic (ROC) analysis. Results: Of 760 cerebral hemorrhage patients enrolled from MIMIC database (Mean age was 68.2 years (SD ± 15.5), 383 (50.4%) patients died in hospital and 377 (49.6%) patients survived. The area under the receiver operating characteristic curve (AUC) of six machine learning algorithms were 0.600 (Nearest Neighbors), 0.617 (Decision Tree), 0.655 (Neural Net), 0.671(AdaBoost), 0.819 (Random Forest), and 0.725 (gcfores) respectively. The AUC was 0.423 for APACHE II score. The Random Forest had the highest specificity and accuracy, as well as the greatest AUC, showing the best ability to predict in-hospital mortality. Conclusions: Compared with conventional scoring system and the other 5 machine learning algorithms in this study, Random Forest algorithm had better performance in predicting in-hospital mortality for cerebral hemorrhage patients in intensive care units, which should be further researched.